Efficiency Effects of Unit-based Pricing Systems and Institutional Choices of Waste Collection - Elbert Dijkgraaf; Raymond Gradus (Tinbergen Institute, 2014)
Much attention has been paid to the influence of the institutional form of waste collection on costs. We extend this literature in three directions by including the unit-based pricing system. First, we show that unit-based pricing systems are more important from a cost-minimizing point of view than the institutional mode of waste collection. In particular, the bag-based and frequency-based pricing systems are preferred. Second, dividing the cost effects between price and quantity effects, we illustrate that lower administrative costs and a smaller waste quantity are the most important drivers of cost decreases. It also shows that a disadvantage of the bag-based system is that it is not easy to price compostable waste. Third, if more general cost functions are analyzed, these estimations suggest that there are economies of scale for small municipalities.
Keywords: H31; H71; Q38; 330; waste collection; cost functions; efficiency; unit-based pricing; contracting out